Pengaruh Pemahaman Pajak dan Transparansi Pajak Pemungutan Nilai Terhadap Kepuasan Pelanggan J&T Express Kota Bandung - Nada Putri Priantina; Hurian Kamela (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study investigates how customer understanding of taxes and transparency of value-added tax (VAT) impact customer satisfaction in J&T Express Bandung City. The study is based on the fact that customer perception of tax costs in expedition services is very important; it is assumed that customer satisfaction can be improved with a good understanding and transparency of VAT calculations. This study uses a quantitative approach and collects data through questionnaires distributed to fifty-eight J&T Express customers in Bandung City. The effect of independent variables (tax understanding and tax transparency) on the dependent variable (customer satisfaction) is measured through PLS-SEM analysis. The results of the study indicate that both factors have a beneficial and significant effect, with tax transparency as the main factor. To increase customer loyalty, this study emphasizes that VAT socialization and clear tax information are needed in transactions.